Islamic Religious Education in the Digital Era: Digital Akhlak Curriculum and Adaptive School Management - Syahruddin, Syahruddin; Nofrizal, Nofrizal; Julhadi, Julhadi; Wahyuni, Sri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
This study aims to analyze the improvement of the quality of Islamic Religious Education in the digital era through the integration of curriculum transformation and adaptive school management. Employing a qualitative approach with a content analysis model, this study utilizes secondary data sources, including academic books, scientific journal articles, conference proceedings, and other relevant literature. Data were selected based on their relevance, credibility, and novelty, and were analyzed using descriptive-analytical techniques through processes of categorization, interpretation, and synthesis to identify patterns and significant conceptual relationships. The findings indicate that improving the quality of Islamic Religious Education in the digital era is closely linked to successful curriculum transformation toward the Digital Akhlak paradigm. This paradigm emphasizes the internalization of Islamic moral values in students’ behavior within digital spaces through the strengthening of critical digital literacy, media ethics, and the contextualization of Islamic teachings in contemporary realities. However, the effectiveness of this curriculum transformation is highly dependent on responsive and visionary school management, particularly in developing teachers’ digital competencies, providing high-quality digital learning infrastructure and content, and implementing academic supervision oriented toward professional development. Without strong managerial support, curriculum innovation risks remaining normative and inadequately implemented. This study highlights that reforming Islamic Religious Education in the digital era requires a holistic approach that integrates curriculum innovation and technology-based school management to foster a generation of Muslims who are faithful, virtuous, critical, and responsible in addressing the challenges of the digital world.